The main types of wind turbinesgenerators in the power supply system - O. V. Pazushkina; M. V. Zolin; I. A. Silkin (Известия высших учебных заведений: Проблемы энергетики)
THE PURPOSE. To consider the problems of protecting equipment of thermal power plants and heat supply systems from internal corrosion. To study the stages of development of domestic deaeration devices and the principles of atmospheric and vacuum deaeration in the framework of the boiler house in Ulyanovsk. To analyze the operation and maintenance of deaerators: DSA-75, AWACS and DV-75 in the boiler house of JSC «Ulyanovsk Cartridge Plant», and in the UMUP «City Heating System».METHODS. When solving this problem, we used an analytical method for evaluating the operation of the DSA-75 atmospheric deaerator and the DV-75 vacuum deaerator.RESULTS. The article presents the main technical characteristics of the atmospheric deaerator DSA-75 and the vacuum deaerator DV-75, and graphical dependencies characterizing the operation of the above deaerators were obtained.CONCLUSION. An analysis of the work of the «AWACS» deaerator showed that this device was never able to take its rightful place as the main and additional deaeration device in the boiler house in Ulyanovsk. Accordingly, the «AWACS» deaerator could not stand on a par with the long-established deaerators developed at CKTI. The authors found that at the present time, at the UMUP «City Heating System» boiler house considered in this article, the water treatment system using the traditional DV-75 vacuum deaerator is well debugged and performs its functions. Thus, high-quality water treatment is ensured in the boiler house.